Understanding the Perceptions of Small-Scale Farmers Towards Hydroponics: A Thematic Analysis - Marie Stephanie E. Velasco; Hannah Joy A. Lanot; Jerson M. Robles; Kyla Mae D. Sacriz; Marianne B. Temporal; Eleonor R. Basilio (International Journal of Environment, Engineering and Education, 2023)
This study examines small farmers' perceptions regarding hydroponic farming systems' utilization. The objectives are to identify key themes and patterns that emerge from farmers' perceptions, understand the factors influencing acceptance or resistance to hydroponics, gain insight into this modern farming technique's potential advantages and challenges, and create informative material to enhance farmers' perceptions of hydroponics. The study aims to provide valuable information to policymakers, researchers, and agricultural industry stakeholders, contributing to a better understanding of hydroponics' feasibility and potential adoption among small-scale farmers. A series of interviews were conducted, and a thorough thematic analysis was employed to identify recurring themes and trends in the perspectives of small-scale farmers on hydroponics. Findings reveal that hydroponics is not accessible to all farmers, with only a tiny percentage familiar with this farming method and its associated benefits. This knowledge is crucial for developing strategies to integrate hydroponics into existing agricultural systems, promote sustainable practices, and support small-scale farmers to improve their living conditions and access food resources. The study's outcomes aim to fill the knowledge gap surrounding small farmers' perceptions of hydroponics, contributing to informed policies, research advancements, and industry practices. By bridging this gap, stakeholders can make informed decisions and create targeted interventions that encourage the adoption of hydroponics as a viable farming technique among small-scale farmers. This research seeks to promote sustainability, resilience and address challenges small farmers face, ensuring their welfare and food security within the agricultural sector.